2002
DOI: 10.1002/cne.10362
|View full text |Cite
|
Sign up to set email alerts
|

Laminar distribution of synaptopodin in normal and reeler mouse brain depends on the position of spine‐bearing neurons

Abstract: Synaptopodin is the first member of a novel class of proline-rich actin-associated proteins. In brain, it is present in the neck of a subset of mature telencephalic spines and is associated closely with the spine apparatus, a Ca(2+) storing organelle within the spine compartment. The characteristic region- and lamina-specific distribution of synaptopodin in rat brain suggested that the distribution pattern of synaptopodin depends on the cytoarchitectonic arrangement of spine-bearing neurons. To test this hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 41 publications
5
21
1
Order By: Relevance
“…SP has been associated with the spine apparatus, a membranous extension of the dendritic smooth endoplasmic reticulum. This neuronal organelle is found in a subpopulation of spines of telencephalic neurons (Spacek, 1985;Spacek and Harris, 1997) and, interestingly, its regional distribution pattern mirrors the expression pattern of SP (Mundel et al, 1997;Deller et al, 2000Deller et al, , 2002. Using immunogold-EM analysis, SP-immunoreactivity was found in close association with the spine apparatus (Deller et al, 2000(Deller et al, , 2003.…”
Section: Discussionmentioning
confidence: 98%
“…SP has been associated with the spine apparatus, a membranous extension of the dendritic smooth endoplasmic reticulum. This neuronal organelle is found in a subpopulation of spines of telencephalic neurons (Spacek, 1985;Spacek and Harris, 1997) and, interestingly, its regional distribution pattern mirrors the expression pattern of SP (Mundel et al, 1997;Deller et al, 2000Deller et al, , 2002. Using immunogold-EM analysis, SP-immunoreactivity was found in close association with the spine apparatus (Deller et al, 2000(Deller et al, , 2003.…”
Section: Discussionmentioning
confidence: 98%
“…Brains were removed and post-fixed in the same fixative for a few hours at 4°C followed by cryoprotection in 20% sucrose in 0.1 M PB, pH 7.4, at 4°C overnight. Cryostat sections (40 m, coronal plane) of the hippocampus were processed for in situ hybridization as described previously (Deller et al, 2002).…”
Section: Materials and Methods Animals And Tissue Preparationmentioning
confidence: 99%
“…Although our previous electron microscopic studies had primarily revealed Synaptopodin in spines where it was associated with the spine apparatus, Synaptopodin immunoreactivity was also observed in the dendritic shafts of some neurons (Deller et al, 2000a(Deller et al, , 2002. Using three-dimensional confocal analysis (Figs.…”
Section: Cellular Distribution Of Synaptopodinpositive Structures In mentioning
confidence: 98%
See 2 more Smart Citations